Facing Death with a Smile: Study on Islamic Counseling in the Da'wa of KH Imam Syairozi Indonesia - Thohir, Mohamad; Hidayat, Rahmat (Proceedings of International Conference on Da'wa and Communication, 2019)
Death is usually considered a frightening specter by most people, so any effort is made to achieve a healthy life, "live all the time". Preaching about death are usually accompanied by images of torture and hell. This paper attempts to present aspects of Islamic counseling in the context of facing death by KH Muhammad Imam Syairozi in his Da'wa . The descriptive qualitative method was used to analyze aspects of Islamic counseling in the video lecture on the Youtube Channel, and was completed with confirmation through direct interviews with the person concerned. This research found 3 new things related to the study of Islamic counseling in the mission of KH Muhammad Imam Syairozi. He uses the "basyiron" strategy, which is giving good news, using analogous examples of daily life behaviors and comprehensive illustrations of human life. Some of the contents of his Da'wa that is interesting include: "The natural world of Barzakh is more perfect than the natural world", "God's creations are many, there is a natural world, natural Barzakh, don’t you want to go there?".